Tinjauan Yuridis Pasal Pemidanaan bagi Pelanggar Rahasia Dagang dalam Undang-Undang Nomor 30 Tahun 2000 - Akram Sri Nerendro Tomo; Burhanudin Burhanudin (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2020)
Abstract.The law number 30 year 2000 about trade secret was first enacted on December 20th 2000. The main purpose of this law is to create a conducive and innovative business climate to create a national and international business competition to be conducive. The other purpose of this law is to protect the rights of the trade secret owners that has not been noticed. To protect the rights of the trade secret owner, the articles of 13 and 14 regulates the elements of violation about trade secrets and then these both articles is accommodated in article 17 abaout the criminal provisions. However, there is a problem in the Article about the punishment due to the inconsistency of the phrase which results in a double understanding of the phrase. The phrase is